FUNGSI STRATEGIS DANAU TONDANO, PERUBAHAN EKOSISTEM DAN MASALAH YANG TERJADI - Euthalia Hanggari Sittadewi (Jurnal Teknologi Lingkungan, 2008)
Tondano is a natural and biggest lake in North Sulawesi which some strategic functions i.e for irrigation, source of drinking water, hydropower, freshwater culture, tourisms, overflow control. Wide of Tondano Lake is about 46 – 51 km2. There are 35 streams as inlet and one outlet only is Tondano Stream. Tondano Lake has some problems caused by many activities both in downstream area or around of the lake. People’s activities such as land clearing for plantation in downstream area, freshwater cultureand daily people’s activities around of the lake had been organic material contribution in the lake waters. It has caused of water hyacinth booming (Eichornia crassipes (Malt) (Soms), erosion and sedimentation. Nowadays water hyacinth has been covered about 20% of Tondano Lake’s wide. Besides reduce of waters quality, water hyacinth booming has been made problems for hydropower and traffic in lake waters to the outlet. Because of that problems, Tondano Lake needs concern for intensif management.Key Words : strategic functions, ecosystem, erosion, sedimentation, water hyacinth.